High-strength and high-rigidity cast aluminum-lithium alloy and preparation method thereof
By using centrifugal casting and smelting furnace and specific chemical composition ratio in the production process of aluminum-lithium alloys, the cast structure with low pore ratio and uniformly distributed nano-scale composite phases are solved, and the insufficient strength and rigidity of existing aluminum-lithium alloys are solved. The lower problem has achieved the production of high-strength and high-stiffness materials, meeting the needs of the aerospace field.
Patent Information
- Application Number
- CN202411605506.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing aluminum-lithium alloys are insufficient in the aerospace field, have low stiffness, and are complex in production processes, which are not suitable for large-scale production, making it difficult to meet the needs of high-strength and high-stiff materials.
High-strength, high-stiffness aluminum-lithium alloy is prepared by centrifugal casting smelting furnace. Through specific chemical composition ratios and process flows, including oxide layer treatment, preheating, vacuum argon filling, staged heating, casting, heat treatment and aging treatment, the low-level Cast structure of pore ratio and uniformly distributed nanoscale composite phase.
The tensile strength and Young's modulus of aluminum-lithium alloys have been significantly improved, reaching more than 450MPa and more than 82GPa, meeting the demand for high-strength and high-stiffness materials in the aerospace field, while simplifying the production process and improving production efficiency.
Smart Images

Figure CN119464848A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof, belonging to the technical field of aluminum-lithium alloy material design and preparation. Background Art
[0002] With the vigorous development of my country's aerospace, weapons and equipment, transportation and other fields, the demand for lightweight, high-strength and high-rigidity alloys has become more and more urgent. Therefore, reducing the density of lightweight alloys and improving strength and rigidity has always been the top priority of aluminum alloy research and development. With the rapid development of aerospace rockets and weapons and equipment towards precision, integrity, lightness, high performance, low cost and short cycle, a large number of high-strength and high-rigidity aluminum alloy components formed by integral casting are used on rockets and weapon models. The casting method using liquid forming has irreplaceable advantages in forming large, complex and thin-walled components, especially the use of near-net-shape aluminum alloy castings. On the one hand, the use of aluminum alloy components as a whole casting instead of multiple parts combined forming significantly improves the overall accuracy and rigidity of the product; on the other hand, the internal structure space of some complex cabins is complex, and the internal cavity processing is very difficult, and even some areas cannot be processed by conventional processing equipment and methods, which requires the use of near-net-shape casting technology; thirdly, the material utilization rate of casting is increased to 60-90%, which not only significantly reduces the amount of mechanical processing, reduces costs, but also shortens the production cycle. Therefore, rockets and equipment use a large number of overall complex high-strength and high-rigidity aluminum alloy castings, and aluminum-lithium alloys occupy a core position in the aerospace field due to their advantages such as low density, high elastic modulus, high specific strength and high specific stiffness, low fatigue crack growth rate, and good high and low temperature performance. However, the most widely used high-strength aluminum alloys in the aerospace field currently include aluminum-zinc alloys, aluminum-copper alloys, and aluminum-copper-lithium alloys, and most of them need to be deformed to achieve higher strength or required shapes. This results in insufficient material utilization, high cost, and long production cycle. In addition, although the strength of these series of aluminum alloys can reach more than 450MPa after deformation processing, the stiffness is still less than 82GPa, which still cannot meet the current demand for high-rigidity aluminum alloys in the aerospace field, and seriously restricts the manufacturing level of my country's military equipment. Therefore, how to design a high-strength and high-rigidity cast aluminum-lithium alloy to meet the needs of large, complex, and thin-walled components, while replacing multiple parts to form and improve the overall accuracy and stiffness of the components has become an urgent problem to be solved.
[0003] Some existing technologies disclose methods for improving the strength and stiffness of aluminum-lithium alloys by using new technologies, deformation processing, and optimizing alloy composition. However, these new technologies cannot mass-produce high-strength and high-stiffness aluminum-lithium alloys, and the production efficiency is low, and the production quality cannot be effectively controlled. Although deformation processing can be mass-produced, the process is complicated and cannot effectively meet the needs of one-piece molding. And the optimized composition still cannot meet the conditions that the aluminum-lithium alloy strength is greater than 450MPa and the stiffness is greater than 82GPa.
[0004] Chinese patent CN113416872A discloses a high-strength and high-toughness aluminum-lithium alloy for aerospace and its preparation method, which adopts the method of spray forming to prepare aluminum-lithium alloy, and adopts the forging process, and combines the first roughening, the second punching and the third hole expansion to prepare the high-strength aluminum-lithium alloy. Although the alloy strength reaches more than 500MPa, the stiffness is only 76GPa, and the subsequent forging process still cannot meet the needs of one-piece forming of structural parts. Chinese patent CN108425050B discloses a high-strength and high-toughness aluminum-lithium alloy and its preparation method, adopts vacuum solvent-free melting casting to obtain high-quality ingots, and obtains high-strength aluminum-lithium alloy through subsequent large deformation and solid solution and aging processes. Although its strength reaches more than 550MPa, its stiffness is unknown. The homogenization, hot rolling, annealing and cold rolling process steps used at the same time are cumbersome, costly, and long cycle, which is not conducive to large-scale production. Chinese patent CN105648283B discloses a low-density, high-rigidity cast aluminum-lithium alloy and its preparation method. The high-rigidity cast aluminum-lithium alloy is obtained by a solid solution aging treatment preparation method. Although the obtained aluminum alloy has a higher elastic modulus and lower density than traditional cast aluminum alloys, its strength is far lower than 450MPa and its rigidity is difficult to exceed 83GPa. Therefore, it is urgent to design and develop a high-strength, high-rigidity and short-production-cycle cast aluminum-lithium alloy. Summary of the invention
[0005] In view of the problems that the current cast aluminum-lithium alloy has insufficient strength, low rigidity, complex production process, is not suitable for large-scale production, and is easily oxidized to form metallurgical defects during the preparation process, the present invention provides a high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof. The chemical composition of the high-strength and high-rigidity cast aluminum-lithium alloy is as follows, by mass percentage: Li 1.5wt.%-3.0wt.%, Cu 1.0wt.%-3.0wt.%, Mg 0.5wt.%-2.0wt.%, Zr0.1wt.%-1.0wt.%, Ti0.1wt.%-1.0wt.%, Ag 0.1wt.%-1.0wt.%, and the balance is Al and unavoidable impurities, and the content of impurity elements is less than 0.1wt.%.
[0006] The high-strength and high-rigidity cast aluminum-lithium alloy is prepared by a centrifugal casting smelting furnace. The cast structure of the aluminum-lithium alloy has a low porosity and a grain size of 5-30μm. The cast grain boundaries are distributed with Al2CuLi, Al2CuMg, Al2LiMg, and Al3Zr, Al3Ti intermetallic compounds. After heat treatment, the matrix is evenly distributed with nano-scale composite phases Al3 (Li, Zr, Ti, Ag, Zn), T1-Al2CuLi, and θ′-Al2Cu precipitation phases. The high-strength and high-rigidity cast aluminum-lithium alloy has the following properties: tensile strength of more than 450MPa and Young's modulus of more than 82GPa.
[0007] The objectives of the present invention are achieved through the following technical solutions.
[0008] A high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof, the method steps are as follows:
[0009] (1) Al-Li master alloy, Al-Cu master alloy, Al-Mg master alloy, Al-Zr master alloy, Al-Ti master alloy, pure aluminum and pure silver are mixed according to the mass ratio of chemical element components of the high-strength and high-rigidity aluminum-lithium alloy.
[0010] (2) First, the surface of the intermediate alloy is treated with an oxide layer and polished with sandpaper. Then, the crucible, mold and raw materials are placed in a high-temperature furnace at 120-250°C for 1-3 hours for preheating. After preheating, the alloy raw materials are placed in the crucible of the centrifugal casting melting furnace.
[0011] (3) First, evacuate the centrifugal casting furnace, then fill it with protective atmosphere, and finally adjust the current of the centrifugal casting furnace to increase the temperature in stages to melt the raw materials in the crucible. After the raw materials in the centrifugal casting furnace are completely melted, keep them warm for 5-20 minutes.
[0012] (4) Set the program of the centrifugal casting melting furnace, stop heating, set the speed to 100-1000r / min, and last for 30-100s to complete the casting.
[0013] (5) After the aluminum-lithium alloy ingot is completely cooled, it is placed in a vacuum heat treatment furnace, the heat treatment furnace is evacuated and filled with protective gas, and then the temperature is raised to perform a secondary solid solution treatment, and then quenching treatment is performed immediately after the completion. Finally, the aluminum-lithium alloy ingot after the solid solution treatment is placed in a vacuum heat treatment furnace for a single-stage aging treatment.
[0014] (6) After the aging treatment, the aluminum-lithium alloy ingot is taken out and placed in air for cooling to obtain a high-strength and high-rigidity aluminum-lithium alloy.
[0015] Furthermore, the mass ratio of chemical element composition of the high-strength and high-rigidity aluminum-lithium alloy in step (1) is characterized in that the Al-Li master alloy is an Al-20wt.%Li master alloy, the Al-Cu master alloy is an Al-50wt.%Cu master alloy, the Al-Mg master alloy is an Al-20wt.%Mg master alloy, the Al-Zr master alloy is an Al-5wt.%Zr master alloy, the Al-Ti master alloy is an Al-10wt.%Ti master alloy, and the pure aluminum content is greater than 99.99%, and the pure silver content is greater than 99.90%.
[0016] Furthermore, step (2) of placing the alloy raw materials in a crucible of a centrifugal casting smelting furnace is characterized in that 1 / 3 of pure aluminum is placed at the bottom of the crucible, Al-Li, Al-Cu, Al-Mg, Al-Zr, Al-Ti and pure Ag are placed in the middle of the crucible, and the remaining pure aluminum is placed on the top.
[0017] Furthermore, the crucible and preheating in step (2) are characterized in that the crucible is a graphite crucible / stainless steel crucible specially coated with boron nitride, wherein the mass fraction of solid boron nitride is greater than 60%, the coating thickness is 0.05 to 1 mm, and then it is allowed to stand at room temperature for 24 to 72 hours; the high-temperature furnace preheats the crucible, mold and raw materials at a heating rate of 5°C / min to 20°C / min.
[0018] Furthermore, the vacuuming of the centrifugal casting melting furnace in step (3) is characterized by: firstly, the pressure in the furnace is evacuated to below 0-0.8 kPa, and this is repeated 2-5 times; then, a protective atmosphere, argon gas, is introduced to make the pressure in the furnace reach 0-40 kPa, and this is repeated 1-3 times. The staged heating steps are as follows: raise the induction heating coil to the top of the crucible, adjust the current of the centrifugal casting melting furnace to 1.0-1.5A, and raise the temperature of the graphite crucible / stainless steel crucible to 200-400°C within 3-6 minutes; then adjust the current of the centrifugal casting melting furnace to 1.5-1.8A, and raise the temperature in the crucible to 400-600°C within 3-8 minutes; then adjust the current of the centrifugal casting melting furnace to 1.8-2.0A, and raise the temperature of the crucible to 650-750°C within 5-10 minutes; then adjust the current of the centrifugal casting melting furnace to 2.0-2.5A, and raise the temperature in the crucible to 750-800°C within 2-5 minutes; finally adjust the current of the centrifugal casting melting furnace to 1.5-2.0A, and stand at 750-780°C for 5-20 minutes.
[0019] Furthermore, the process of setting the centrifugal casting furnace in step (4) to stop heating for centrifugal casting is characterized in that the current of the centrifugal casting furnace is adjusted to 0A, and the induction heating coil is lowered to the bottom of the crucible. The centrifugal casting mold is a copper mold, and the wall thickness of the copper mold is more than 40mm.
[0020] Further, the high-strength and high-rigidity aluminum-lithium alloy heat treatment described in step (5) is characterized in that the secondary solution treatment includes: first, keeping the temperature at 420°C to 480°C for 2h to 10h, then heating to 500°C to 530°C for 2h to 6h, and the heating rate is 5°C / min to 20°C / min. Secondly, the cooling method in step (6) is water cooling or oil cooling, the quenching oil component is dimethyl silicone oil, the viscosity is 100CS, and the quenching oil or water temperature is 10°C to 30°C. Preferably, the aluminum-lithium alloy is transferred from the heat treatment furnace of 500°C to 530°C to water or oil at 10°C to 30°C within 5s to 20s. The heating rate of the heat treatment furnace is preferably 5°C / min to 20°C / min, and the vacuum heat treatment furnace is evacuated to below 1kPa, repeated 1-3 times, and filled with argon to atmospheric pressure.
[0021] Furthermore, the aging treatment in step (6) is characterized by: keeping the temperature at 150°C to 190°C for 12h to 72h, with a heating rate of 5°C / min to 20°C / min. The aluminum-lithium alloy is transferred from the heat treatment furnace at 150°C to 190°C to air within 5s to 20s.
[0022] Beneficial effects:
[0023] The present invention provides a high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof, which effectively reduces the hole defects generated during the casting process, obtains a fine-grained structure, and the two-stage solid solution process and the single-stage aging process significantly improve the strength and rigidity of the cast aluminum-lithium alloy, which is conducive to expanding the application of aluminum-lithium alloys in military fields such as aerospace. At the same time, the method and equipment of the present invention are simple to operate and have high production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the microstructure diagram of the high-strength and high-rigidity cast aluminum-lithium alloy after step (4) of Example 1.
[0025] Figure 2 This is the microstructure diagram of the high-strength and high-rigidity cast aluminum-lithium alloy after step (4) of Example 2.
[0026] Figure 3 This is the microstructure diagram of the high-strength and high-rigidity cast aluminum-lithium alloy after step (6) of Example 3.
[0027] Figure 4 This is the microstructure diagram of the high-strength and high-rigidity cast aluminum-lithium alloy after step (6) of Example 4. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific implementation methods, wherein the methods described are all methods of the present invention unless otherwise specified.
[0029] Example 1
[0030] A high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof, comprising the following steps:
[0031] (1) Al-20wt.% Li master alloy, Al-50wt.% Cu master alloy, Al-20wt.% Mg master alloy, Al-5wt.% Zr master alloy, Al-10wt.% Ti master alloy, and pure aluminum with a content greater than 99.99% and pure silver with a content greater than 99.90% are mixed according to the mass ratio of the chemical element components of the high-strength and high-rigidity cast aluminum-lithium alloy.
[0032] (2) First, the surface of the intermediate alloy is treated with an oxide layer and polished with sandpaper. Then, the graphite crucible coated with boron nitride, the copper mold and the raw materials are placed in a high-temperature furnace for preheating at 120°C for 3 hours. After preheating, the alloy raw materials are placed in the crucible of the centrifugal casting melting furnace.
[0033] (3) First, evacuate the centrifugal casting melting furnace to a pressure below 0.5 kPa, repeat twice, then introduce a protective atmosphere, argon, to make the furnace pressure reach 40 kPa, repeat twice. Raise the induction heating coil to the top of the crucible, adjust the current of the centrifugal casting melting furnace to 1.2 A, and raise the graphite crucible to 350 ° C within 5 minutes; then adjust the current of the centrifugal casting melting furnace to 1.5 A, and raise the temperature in the crucible to 500 ° C within 5 minutes; then adjust the current of the centrifugal casting melting furnace to 1.8 A, and raise the temperature of the crucible to 700 ° C within 8 minutes; then adjust the current of the centrifugal casting melting furnace to 2.0 A, and raise the temperature in the crucible to 750 ° C within 2 minutes; finally adjust the current of the centrifugal casting melting furnace to 1.8 A and let it stand at 750 ° C for 5 minutes.
[0034] (4) Setting the program of the centrifugal casting melting furnace, adjusting the current of the centrifugal casting melting furnace to 0 A, stopping heating, lowering the induction heating coil to the bottom of the crucible, setting the speed to 300 r / min, and continuing the time for 40 s to complete the casting.
[0035] (5) After the aluminum-lithium alloy ingot is completely cooled, it is placed in a vacuum heat treatment furnace, and the heat treatment furnace is evacuated to below 0.8 kPa, repeated twice, and filled with argon to atmospheric pressure. Then a secondary solid solution treatment is performed, first at 450 ° C for 4 hours, then heated to 510 ° C for 3 hours, and the heating rate is 10 ° C / min. Finally, the aluminum-lithium alloy is transferred from the 510 ° C heat treatment furnace to 25 ° C water within 5 seconds for quenching.
[0036] (6) After the solution treatment is completed, the solution-treated aluminum-lithium alloy is placed in a heat treatment furnace and kept at 175°C for 24 hours at a heating rate of 10°C / min. After the insulation is completed, the aluminum-lithium alloy is transferred from the 175°C heat treatment furnace to air within 5 seconds to obtain a high-strength and high-rigidity aluminum-lithium alloy.
[0037] The composition and mass percentage of the high-strength and high-rigidity aluminum-lithium alloy prepared in this embodiment are as follows: Li 2.45wt.%, Cu 1.60wt.%, Mg 0.66wt.%, Zr 0.12wt.%, Ti 0.24wt.%, Ag 0.41wt.% and the balance Al, etc.
[0038] from Figure 1 It can be seen that after step (4), the aluminum-lithium alloy grains are equiaxed grains with an average grain size of 10.1 μm and almost no void defects. The tensile strength of the aluminum-lithium alloy after cooling in step (7) is measured to be 493.20 MPa and the Young's modulus is 84.54 GPa.
[0039] Example 2
[0040] A high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof, comprising the following steps:
[0041] (1) Al-20wt.% Li master alloy, Al-50wt.% Cu master alloy, Al-20wt.% Mg master alloy, Al-5wt.% Zr master alloy, Al-10wt.% Ti master alloy, and pure aluminum with a content greater than 99.99% and pure silver with a content greater than 99.90% are mixed according to the mass ratio of the chemical element components of the high-strength and high-rigidity cast aluminum-lithium alloy.
[0042] (2) First, the surface of the intermediate alloy is treated with an oxide layer and polished with sandpaper. Then, the graphite crucible coated with boron nitride, the copper mold and the raw materials are placed in a high-temperature furnace and preheated at 200°C for 2 hours. After preheating, the alloy raw materials are placed in the crucible of the centrifugal casting melting furnace.
[0043] (3) First, evacuate the centrifugal casting melting furnace to a pressure below 0.1 kPa, repeat 3 times, then introduce a protective atmosphere, argon, to make the furnace pressure reach 30 kPa, repeat 3 times. Raise the induction heating coil to the top of the crucible, adjust the current of the centrifugal casting melting furnace to 1.0 A, and raise the graphite crucible to 300 ° C within 5 minutes; then adjust the current of the centrifugal casting melting furnace to 1.6 A, and raise the temperature in the crucible to 520 ° C within 6 minutes; then adjust the current of the centrifugal casting melting furnace to 1.9 A, and raise the temperature of the crucible to 720 ° C within 8 minutes; then adjust the current of the centrifugal casting melting furnace to 2.2 A, and raise the temperature in the crucible to 780 ° C within 2 minutes; finally adjust the current of the centrifugal casting melting furnace to 1.8 A, and let it stand at 780 ° C for 10 minutes.
[0044] (4) Setting the program of the centrifugal casting melting furnace, adjusting the current of the centrifugal casting melting furnace to 0 A, stopping heating, lowering the induction heating coil to the bottom of the crucible, setting the speed to 400 r / min, and continuing the time for 30 s to complete the casting.
[0045] (5) After the aluminum-lithium alloy ingot obtained after casting is completely cooled, it is placed in a vacuum heat treatment furnace, and the heat treatment furnace is evacuated to below 0.5 kPa, repeated 3 times, and filled with argon to atmospheric pressure. Then a secondary solid solution treatment is performed, first at 450 ° C for 6 hours, then heated to 530 ° C for 2 hours, and the heating rate is 10 ° C / min. Finally, the aluminum-lithium alloy is transferred from the 530 ° C heat treatment furnace to 25 ° C water within 5 seconds for quenching.
[0046] (6) After the solution treatment is completed, the solution-treated aluminum-lithium alloy is placed in a heat treatment furnace and kept at 175°C for 48 hours at a heating rate of 10°C / min. After the insulation is completed, the aluminum-lithium alloy is transferred from the 175°C heat treatment furnace to air within 5 seconds to obtain a high-strength and high-rigidity aluminum-lithium alloy.
[0047] The composition and mass percentage of the high-strength and high-rigidity aluminum-lithium alloy prepared in this embodiment are as follows: Li 1.95wt.%, Cu 1.57wt.%, Mg 0.75wt.%, Zr 0.13wt.%, Ti 0.30wt.%, Ag 0.38wt.% and the balance Al, etc.
[0048] from Figure 2 It can be seen that after step (4), the aluminum-lithium alloy grains are equiaxed grains with an average grain size of 27.8 μm and almost no void defects. The tensile strength of the aluminum-lithium alloy after cooling in step (7) is measured to be 461.71 MPa and the Young's modulus is 82.10 GPa.
[0049] Example 3
[0050] A high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof, comprising the following steps:
[0051] (1) Al-20wt.% Li master alloy, Al-50wt.% Cu master alloy, Al-20wt.% Mg master alloy, Al-5wt.% Zr master alloy, Al-10wt.% Ti master alloy, and pure aluminum with a content greater than 99.99% and pure silver with a content greater than 99.90% are mixed according to the mass ratio of the chemical element components of the high-strength and high-rigidity cast aluminum-lithium alloy.
[0052] (2) First, the surface of the intermediate alloy is treated with an oxide layer and polished with sandpaper. Then, the stainless steel crucible coated with boron nitride, the copper mold and the raw materials are placed in a high-temperature furnace for preheating at 180°C for 1.5 hours. After preheating, the alloy raw materials are placed in the crucible of the centrifugal casting melting furnace.
[0053] (3) First, evacuate the centrifugal casting melting furnace to a pressure below 0.5 kPa, repeat twice, then introduce a protective atmosphere, argon, to make the furnace pressure reach 20 kPa, repeat twice. Raise the induction heating coil to the top of the crucible, adjust the current of the centrifugal casting melting furnace to 1.0 A, and raise the graphite crucible to 300 ° C within 5 minutes; then adjust the current of the centrifugal casting melting furnace to 1.6 A, and raise the temperature in the crucible to 520 ° C within 6 minutes; then adjust the current of the centrifugal casting melting furnace to 1.9 A, and raise the temperature of the crucible to 720 ° C within 8 minutes; then adjust the current of the centrifugal casting melting furnace to 2.2 A, and raise the temperature in the crucible to 780 ° C within 2 minutes; finally adjust the current of the centrifugal casting melting furnace to 1.8 A, and let it stand at 760 ° C for 10 minutes.
[0054] (4) Setting the program of the centrifugal casting melting furnace, adjusting the current of the centrifugal casting melting furnace to 0 A, stopping heating, lowering the induction heating coil to the bottom of the crucible, setting the speed to 500 r / min, and continuing the time for 30 s to complete the casting.
[0055] (5) After the aluminum-lithium alloy ingot is completely cooled, it is placed in a vacuum heat treatment furnace, and the heat treatment furnace is evacuated to below 0.2 kPa, repeated twice, and filled with argon to atmospheric pressure. Then a secondary solid solution treatment is performed, first at 480 ° C for 4 hours, then heated to 520 ° C for 4 hours, and the heating rate is 10 ° C / min. Finally, the aluminum-lithium alloy is transferred from the 520 ° C heat treatment furnace to 25 ° C oil within 5 seconds for quenching.
[0056] (6) After the solution treatment is completed, the solution-treated aluminum-lithium alloy is placed in a heat treatment furnace and kept at 150°C for 36 hours at a heating rate of 10°C / min. After the insulation is completed, the aluminum-lithium alloy is transferred from the 150°C heat treatment furnace to air within 5 seconds to obtain a high-strength and high-rigidity aluminum-lithium alloy.
[0057] The composition and mass percentage of the high-strength and high-rigidity aluminum-lithium alloy prepared in this embodiment are as follows: Li 2.35wt.%, Cu 1.98wt.%, Mg 0.80wt.%, Zr 0.10wt.%, Ti 0.25wt.%, Ag 0.35wt.% and the balance Al, etc.
[0058] from Figure 3 It can be seen that after step (6), a small amount of Al2CuLi, Al2CuMg, Al2LiMg, and Al3Zr, Al3Ti intermetallic compounds exist in the aluminum-lithium alloy. The tensile strength of the aluminum-lithium alloy after cooling in step (7) is measured to be 451.60MPa, and the Young's modulus is 83.76GPa.
[0059] Example 4
[0060] A high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof, comprising the following steps:
[0061] (1) Al-20wt.% Li master alloy, Al-50wt.% Cu master alloy, Al-20wt.% Mg master alloy, Al-5wt.% Zr master alloy, Al-10wt.% Ti master alloy, and pure aluminum with a content greater than 99.99% and pure silver with a content greater than 99.90% are mixed according to the mass ratio of the chemical element components of the high-strength and high-rigidity cast aluminum-lithium alloy.
[0062] (2) First, the surface of the intermediate alloy is treated with an oxide layer and polished with sandpaper. Then, the stainless steel crucible coated with boron nitride, the copper mold and the raw materials are placed in a high-temperature furnace and preheated at 150°C for 2.5 hours. After preheating, the alloy raw materials are placed in the crucible of the centrifugal casting melting furnace.
[0063] (3) First, evacuate the centrifugal casting melting furnace to a pressure below 0.1 kPa, repeat once, then introduce a protective atmosphere, argon, to make the furnace pressure reach 20 kPa, repeat once. Raise the induction heating coil to the top of the crucible, adjust the current of the centrifugal casting melting furnace to 1.5 A, and raise the graphite crucible to 400 ° C within 3 minutes; then adjust the current of the centrifugal casting melting furnace to 1.8 A, and raise the temperature in the crucible to 600 ° C within 3 minutes; then adjust the current of the centrifugal casting melting furnace to 2.0 A, and raise the temperature of the crucible to 750 ° C within 5 minutes; then adjust the current of the centrifugal casting melting furnace to 2.5 A, and raise the temperature in the crucible to 800 ° C within 2 minutes; finally adjust the current of the centrifugal casting melting furnace to 2.0 A and let it stand at 780 ° C for 5 minutes.
[0064] (4) Setting the program of the centrifugal casting melting furnace, adjusting the current of the centrifugal casting melting furnace to 0 A, stopping heating, lowering the induction heating coil to the bottom of the crucible, setting the speed to 800 r / min, and continuing for 60 s to complete the casting.
[0065] (5) After the aluminum-lithium alloy ingot obtained after casting is completely cooled, it is placed in a vacuum heat treatment furnace, and the heat treatment furnace is evacuated to below 0.8 kPa, repeated 4 times, and filled with argon to atmospheric pressure. Then a secondary solid solution treatment is performed, first at 480 ° C for 10 hours, then heated to 530 ° C for 6 hours, and the heating rate is 10 ° C / min. Finally, the aluminum-lithium alloy is transferred from the 530 ° C heat treatment furnace to 25 ° C oil within 5 seconds for quenching.
[0066] (6) After the solution treatment is completed, the solution-treated aluminum-lithium alloy is placed in a heat treatment furnace and kept at 190°C for 72 hours at a heating rate of 10°C / min. After the insulation is completed, the aluminum-lithium alloy is transferred from the 190°C heat treatment furnace to air within 5 seconds to obtain a high-strength and high-rigidity aluminum-lithium alloy.
[0067] The composition and mass percentage of the high-strength and high-rigidity aluminum-lithium alloy prepared in this embodiment are as follows: Li 2.55wt.%, Cu 1.51wt.%, Mg 1.20wt.%, Zr 0.20wt.%, Ti 0.25wt.%, Ag 0.45wt.% and the balance Al, etc.
[0068] from Figure 4 It can be seen that after step (6), a small amount of Al2CuLi, Al2CuMg, Al2LiMg, Al3Zr, and Al3Ti intermetallic compounds exist in the aluminum-lithium alloy. The tensile strength of the aluminum-lithium alloy after cooling in step (7) is measured to be 451.11 MPa, and the Young's modulus is 84.01 GPa.
[0069] The heat treatment mechanical properties parameters of the aluminum-lithium alloy in the embodiment are as follows:
[0070] state Tensile strength(MPa) Young's modulus(GPa) Example 1 493.20 84.54 Example 2 461.71 82.10 Example 3 451.60 83.76 Example 4 453.11 84.01
[0071] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method thereof, characterized in that: The aluminum-lithium alloy composition is composed of Li 1.5wt.%-3.0wt.%, Cu 1.0wt.%-3.0wt.%, Mg 0.5wt.%-2.0wt.%, Zr0.1wt.%-1.0wt.%, Ti 0.1wt.%-1.0wt.%, Ag 0.1wt.%-1.0wt.%, and the remainder is Al and unavoidable impurities, and the content of impurity elements is less than 0.1wt.%.
2. A high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method according to claim 1, characterized in that: The high-strength and high-rigidity cast aluminum-lithium alloy has a cast grain size of 5-30 μm, and Al2CuLi, Al2CuMg, Al2LiMg, Al3Zr, and Al3Ti intermetallic compounds are distributed at the grain boundaries. After heat treatment, nanoscale composite phases Al3 (Li, Zr, Ti, Ag, Zn), T1-Al2CuLi, and θ′-Al2Cu precipitation phases are uniformly distributed in the matrix.
3. A high-strength and high-rigidity cast aluminum-lithium alloy and preparation method according to claim 1, characterized in that: The high-strength and high-rigidity cast aluminum-lithium alloy and its preparation method have a tensile strength of more than 450 MPa and a Young's modulus of more than 82 GPa.
4. A high-strength and high-rigidity cast aluminum-lithium alloy and a preparation method according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Al-Li master alloy, Al-Cu master alloy, Al-Mg master alloy, Al-Zr master alloy, Al-Ti master alloy, pure aluminum and pure silver are mixed according to the mass ratio of chemical element components of the high-strength and high-rigidity cast aluminum-lithium alloy. (2) First, the surface of the intermediate alloy is treated with an oxide layer and polished with sandpaper. Then, the crucible, mold and raw materials are placed in a high-temperature furnace at 120-250°C for 1-3 hours for preheating. After preheating, the alloy raw materials are placed in the crucible of the centrifugal casting melting furnace. (3) First, evacuate the centrifugal casting furnace, then fill it with protective atmosphere, and finally adjust the power of the centrifugal casting furnace to increase the temperature in stages to melt the raw materials in the crucible. After the raw materials in the centrifugal casting furnace are completely melted, keep them warm for 5-20 minutes. (4) Set the program of the centrifugal casting melting furnace, stop heating, set the speed to 100-1000r / min, and last for 30-100s to complete the casting. (5) After the aluminum-lithium alloy ingot is completely cooled, it is placed in a vacuum heat treatment furnace, the heat treatment furnace is evacuated and filled with protective gas, and then the temperature is raised to perform a secondary solid solution treatment, and then quenching treatment is performed immediately after the completion. Finally, the aluminum-lithium alloy ingot after the solid solution treatment is placed in a vacuum heat treatment furnace for a single-stage aging treatment. (6) After the aging treatment, the aluminum-lithium alloy ingot is taken out and placed in air for cooling to obtain a high-strength and high-rigidity aluminum-lithium alloy.
5. According to the mass ratio of chemical element components of the high-strength and high-rigidity cast aluminum-lithium alloy in step (1) described in claim 4, the Al-Li master alloy is Al-20wt.%Li master alloy, the Al-Cu master alloy is Al-50wt.%Cu master alloy, the Al-Mg master alloy is Al-20wt.%Mg master alloy, the Al-Zr master alloy is Al-5wt.%Zr master alloy, the Al-Ti master alloy is Al-10wt.%Ti master alloy, and the pure aluminum content is greater than 99.99%, and the pure silver content is greater than 99.90%.
6. The method of placing the alloy raw materials in the crucible of the centrifugal casting smelting furnace in step (2) according to claim 4 is characterized in that 1 / 3 of pure aluminum is placed at the bottom of the crucible, Al-Li, Al-Cu, Al-Mg, Al-Zr, Al-Ti intermediate alloys and pure silver are placed in the middle of the crucible, and the remaining pure aluminum is placed on the top.
7. The crucible and preheating in step (2) according to claim 4 are characterized in that the crucible is a graphite crucible / stainless steel crucible specially coated with boron nitride, wherein the mass fraction of solid boron nitride is greater than 60%, the coating thickness is 0.05-1 mm, and then it is left to stand at room temperature for 24-72 hours; the heating rate of the high-temperature furnace preheating the crucible, mold and raw materials is 5°C / min-20°C / min.
8. The vacuuming of the centrifugal casting melting furnace in step (3) of claim 4 is characterized by: firstly, the pressure in the furnace is evacuated to below 0-0.8 kPa, and this is repeated 2-5 times; then, a protective atmosphere, argon gas, is introduced to make the pressure in the furnace reach 0-40 kPa, and this is repeated 1-3 times. The staged heating steps are as follows: raise the induction heating coil to the top of the crucible, adjust the current of the centrifugal casting melting furnace to 1.0-1.5A, and raise the temperature of the graphite crucible / stainless steel crucible to 200-400°C within 3-6 minutes; then adjust the current of the centrifugal casting melting furnace to 1.5-1.8A, and raise the temperature in the crucible to 400-600°C within 3-8 minutes; then adjust the current of the centrifugal casting melting furnace to 1.8-2.0A, and raise the temperature of the crucible to 650-750°C within 5-10 minutes; then adjust the current of the centrifugal casting melting furnace to 2.0-2.5A, and raise the temperature in the crucible to 750-800°C within 2-5 minutes; finally adjust the current of the centrifugal casting melting furnace to 1.5-2.0A, and stand at 750-780°C for 5-20 minutes.
9. The process of setting the centrifugal casting furnace in step (4) of claim 4 to stop heating for centrifugal casting is characterized in that the current of the centrifugal casting furnace is adjusted to 0A, and the induction heating coil is lowered to the bottom of the crucible. The centrifugal casting mold is a copper mold with a wall thickness of more than 40 mm.
10. The high-strength and high-rigidity aluminum-lithium alloy heat treatment in step (5) according to claim 4 is characterized in that the secondary solution treatment comprises: First, keep the temperature at 420℃~480℃ for 2h~10h, then heat it to 500℃~530℃ and keep it for 2h~6h, and the heating rate is 5℃ / min~20℃ / min. Secondly, the cooling method in step (6) is water cooling or oil cooling, the quenching oil component is dimethyl silicone oil, the viscosity is 100CS, and the quenching oil or water temperature is 10℃~30℃. Preferably, the aluminum-lithium alloy is transferred from the heat treatment furnace of 500℃~530℃ to water or oil of 10℃~30℃ within 5s~20s. The heating rate of the heat treatment furnace is preferably 5℃ / min~20℃ / min, and the vacuum heat treatment furnace is evacuated to below 1kPa, repeated 1-3 times, and filled with argon to atmospheric pressure.
11. The aging treatment in step (6) of claim 4 is characterized by: keeping the temperature at 150°C to 190°C for 12h to 72h, with a heating rate of 5°C / min to 20°C / min. The aluminum-lithium alloy is transferred from the heat treatment furnace at 150°C to 190°C to air within 5s to 20s.
Citation Information
Patent Citations
Low-density, high-rigidity cast aluminum-lithium alloy and preparation method thereof
CN105648283B
A high-strength and high-toughness aluminum-lithium alloy and its preparation method
CN108425050B
High-strength and high-toughness aluminum-lithium alloy for spaceflight and preparation method thereof
CN113416872A